Antibody Response to Canine Parvovirus Vaccination in Dogs with Hyperadrenocorticism Treated with Trilostane - Michèle Bergmann; Monika Freisl; Katrin Hartmann; Stephanie Speck; Uwe Truyen; Yury Zablotski; Matthias Mayr; Astrid Wehner (Vaccines, 2020)
It is unknown how dogs with hyperadrenocorticism (HAC) respond to vaccination. This study measured antibodies against canine parvovirus (CPV) in dogs with HAC treated with trilostane before and after CPV vaccination, and compared the immune response to that from healthy dogs. Eleven dogs with HAC, and healthy age-matched control dogs (n = 31) received a modified-live CPV vaccine. Antibodies were determined on days 0, 7, and 28 by hemagglutination inhibition. Univariate analysis was used to compare the immune response of dogs with HAC and healthy dogs. Pre-vaccination antibodies (≥10) were detected in 100% of dogs with HAC (11/11; 95% CI: 70.0–100) and in 93.5% of healthy dogs (29/31; 95% CI: 78.3–99.2). No ≥4-fold increase in antibody titer was observed in dogs with HAC while in 22.6% of healthy dogs, a ≥4-fold titer increase was observed (7/31; 95% CI: 11.1–40.1). Mild vaccine-associated adverse events (VAAEs) were detected in 54.5% of dogs with HAC (6/11; 95% CI: 28.0–78.8) and in 29.0% of healthy dogs (9/31; 95% CI: 15.9–46.8). There was neither a significant difference in presence of pre-vaccination antibodies (p = 1.000), or response to vaccination (p = 0.161), nor in the occurrence of VAAEs (p = 0.158). Immune function of dogs with HAC treated with trilostane seems comparable to that of healthy dogs.